Kontrol Jarak Jauh Sistem Irigasi Sawah Berbasis Internet Of Things (IoT) - Sugiono, Sugiono; Indriyani, Tutuk; Ruswiansari, Maretha (INTEGER: Journal of Information Technology, 2017)
. IrrigationÂ  systems in Indonesia are mostly carried out manually in which opening and closing of irrigation channel to rice field are done in traditional way. Internet of Things (IoT)-based control system on irrigation with Wemos D1 ESP8266is a device designed for assisting farmers to ease water irrigation to their rice fields from far away in the real-time. This device aims at improving the farmer effectiveness in working. It used servo motor as the hardware for portal functioning to obtain data from the water height by HC-SR04 ultrasonic sensor as well as serving the control centre by Wemos D1 ESP8266 microcontroller. The control system of irrigation portal was carried out by android application which connected to node controller trough apy key from web hosting. After the portal was opened, the data of water height from controller node was sent and displayed in application. The process of system controlling can be done wher ever and whenever as long as there is a real-time internet connection. The system testing used rice field prototype as the test parameter for the success of control and connectivity functionality. The test employed 3 different connectivity which yielded control delay average with different provider speeds i.e 5.819 seconds, 3.545 seconds, and 7.333 seconds after the controlling process from application.Keywords : android, apy key, Internet of Things, internet, Wemos D1 R2, control.